Radar equations for modern radar - Barton, David Knox, 1927- (Artech House, 2013)
Based on the classic, "Radar Range-Performance Analysis from 1980," this practical volume extends that work to ensure applicability of radar equations to the design and analysis of modern radars. This book helps you identify what information on the radar and its environment is needed to predict detection range. Moreover, it provides equations and data to improve the accuracy of range calculations. You find detailed information on propagation effects, methods of range calculation in environments that include clutter, jamming and thermal noise, as well as loss factors that reduce radar performance. This book is supported with nearly 200 illustrations and over 430 equations. -- Edited summary from book.
Keywords: Radar.; elektronické knihy; electronic books